1980
DOI: 10.21273/jashs.105.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Apple Bloom Date on Maturity and Storage Quality of ‘Starking Delicious’ Apples1

Abstract: Tree cages were used to modify temperature around ‘Starking Delicious’ apple (Malus domestica Borkh.) trees and to establish 4 bloom dates: April 2, 15 and May 7, 22. Determination of soluble solids, acid, firmness and chlorophyll indicated that the time from bloom to maturity was longer for fruit from earlier than normal bloom. Fruit from delayed bloom accumulated less soluble solids than that from normal or earlier bloom dates. Ultimate fruit size decreased with each successive bloom. Fruit from the 2 early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous chamber studies that used several of the other widely grown apple cultivars showed that the values of acidity (Tromp, 1997;Yamada et al, 1994), watercore (Yamada et al, 1994), blush (Blankenship, 1987;Honda et al, 2014), ground color (Olsen and Martin, 1980), and starch disappearance (Yamada et al, 1994) decreased with higher air temperatures, whereas sugar content and firmness did not change (Blankenship, 1987;Tromp, 1997). Therefore, these temperature responses are common in many cultivars.…”
Section: Air Temperature Effects On Quality Indicesmentioning
confidence: 96%
“…Previous chamber studies that used several of the other widely grown apple cultivars showed that the values of acidity (Tromp, 1997;Yamada et al, 1994), watercore (Yamada et al, 1994), blush (Blankenship, 1987;Honda et al, 2014), ground color (Olsen and Martin, 1980), and starch disappearance (Yamada et al, 1994) decreased with higher air temperatures, whereas sugar content and firmness did not change (Blankenship, 1987;Tromp, 1997). Therefore, these temperature responses are common in many cultivars.…”
Section: Air Temperature Effects On Quality Indicesmentioning
confidence: 96%
“…Addition of Cu and Co increased scald, while Ba and Sr reduced the disorder (71). Cultivar susceptibility (50,54), rootstocks (54), eth ylene levels in storage (37,45), preharvest temperatures (1,52,55), orchard locality (43), ventilation and air movement in storage (34), and storage conditions (12,44) are some other factors influencing the susceptibility of ap ples to scald.…”
Section: Factors Influencing the Susceptibility Of Apples To Scaldmentioning
confidence: 99%
“…In apples, the largest and highest-quality fruit come from early-opened or pollinated blossoms (13,19), the first (terminal) bloom within a cluster (20), the youngest spurs (10, 18), and largest fruit at an early reference date (3). Physiological maturity is more advanced for fruit from interior rather than exterior positions of the tree (9, 11) or near a " ring scar" (bud scale scar) (6).…”
mentioning
confidence: 99%